Seas No Longer Divide - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2021)
A three-part historic paper by Alan Tulip in the Telecommunication Journal of Australia in 1988 describes the political campaign for the connection of Tasmania to the Australian mainland telecommunications network after World War I, not completed until 1936.